(untitled) (Journal of Economic Research & Business Administration, 2015)
In article multinational corporations are considered as factors of process of globalization. The multinational companies have high level of centralization. They use filial system of the organization and treat economically and intelligently powerful diversified companies. The international regional and branch movement of the capital is peculiar to them. Process of transnationalization is considered as expansion or the international activity of industrial firms, banks, the companies in the field of rendering services; it leads to transformation of the national company to the transnational. It is characterizad as creation joints the companies, attraction of financial means of foreign banks, concentration of the capital at the expense of merger of firms in other countries. In the modern world multinational corporations – having high extent of centralization, economically and intelligently powerfull diversified companies wnich use filial system of the organization, the international regional and branch movement of the capital is pecuilar to them.